(untitled) (Revista cientifica In Vestigium Ire, 2021)
While organizational theory generally recognizes the positive influence of corporate social responsibility (CSR) on organizational performance, the latent factors as to how or why CSR leads to improved organizational performance remain to be elucidated. In this regard, it is argued that organizational employees are an important mechanism in CSR value creation. The objective of the research was to analyze the CSR of agricultural organizations in Mexico, and its relationship with organizational performance. Based on stakeholder theory, we explored whether employees relate to business performance, as seen through agricultural exports. The data were obtained from 95 Mexican agroindustrial companies that participate in the Socially Responsible Company label granted by the Mexican Center for Philanthropy (CEMEFI). Using the bilogit logistic regression technique, results were obtained which suggest that employees have a positive influence on the participation of these companies in export markets. In addition, this organizational performance was also related to the implementation of fair labor practices, ethical commitment and care for the environment.